General molecular and cellular mechanisms for renal and cardiac remodeling in chronic kidney disease: a target for nephrocardioprotection - L V Kozlovskaia (Терапевтический архив, 2013)
The lecture considers a number of molecular and cellular mechanisms underlying the structural and functional rearrangement and development of renal and cardiac fibrosis in chronic kidney disease (CKD). It details the key component of disadaptative organ remodeling (the formation of myofibroblasts via epithelial-mesenchymal and endothelial-mesenchymal transdifferentiation) and the role of leading angiofibrogenic mediators (angiotensin II, transforming growth factor-Β type 1, a plasminogen activator inhibitor type 1, etc.) in the regulation of these processes. Investigation of the molecular and cellular bases of organ fibrosis, including the factors of dysregulated activation, differentiation and survival of microfibroblasts, makes it possible to specify the mechanisms of action of traditional nephro- and cardioprotective agents, to offer a possibility for a goal-oriented (target) effect on individual fibrogenic components, and to expand the arsenal of medications suppressing renal and cardiac remodeling.